The Effectiveness of Poetry Reading Learning using Draladater Model on Extrovert and Introvert Senior High School Students (Universitas Negeri Semarang, 2018)
The purpose of this study was to examine the effectiveness of poetry reading learning using draladater model on high school students with extrovert personality, examine the effectiveness of poetry reading learning using draladater model on high school students introvert personality, and investigate the comparison of the effectiveness of poetry reading learning using draladater model on extrovert and introvert personality students. To achieve these purposes, this study used quasi experimental design (Non Equivalent Control Group Design). Meanwhile, the samples of this study were taken from the ability of students’ poetry reading in class X or tenth grade of State Senior High School (SMA Negeri) 1 Kajen and State Senior High School (SMA Negeri) 1 Wiradesa. The results of this study showed that the mean score of the posttess of poetry reading learning by using draladater model on extrovert personality of 82.3, while the mean score of poetry reading learning with draladater model on introvert personality student was 77.4. It shows that the average score of poetry reading with draladater model on extrovert personality student was greater than on introvert students. Thus, poetry reading learning with draladater model is more effective to be applied on extrovert personality students than the introvert one.